Diagnostic Considerations in Acute Disseminated Encephalomyelitis and the Interface with MOG Antibody - Santoro, Jonathan D.; Chitnis, Tanuja (Neuropediatrics, 2019)
Acute disseminated encephalomyelitis (ADEM) is a common yet clinically heterogenous syndrome characterized by encephalopathy, focal neurologic findings, and abnormal neuroimaging. Differentiating ADEM from other demyelinating disorders of childhood can be difficult and appropriate interpretation of the historical, clinical, and neurodiagnostic components of a patient's presentation is critical. Myelin oligodendrocyte glycoprotein (MOG) antibody-associated diseases are a recently recognized set of disorders, which include ADEM presentations, among other phenotypes. This review article discusses the clinical diagnosis, differential diagnosis, interpretation of data, and treatment/prognosis of this unique syndrome with distinctive review of the spectrum of MOG antibodies.
Keywords: ADEM; acute disseminated encephalomyelitis; diagnosis; treatment; MOG antibody